Understanding of Circular Processes and Its Impact on Indian Economy - KAPOOR, NAMITA; JAUHARI, DR. SANGEETA; MAHESHWARI, DR. DEEPTI (The journal of contemporary issues in business and government, 2021)
This paper aims at identifying the main processes in the circular economy based on review of definitions given by different eminent researchers. These processes can be adopted and implemented by business entities and policy makers to achieve the desired effects. These effects may include not only environment but also economic and social. These processes may be practiced by businesses to achieve circularity and shift from the traditional linear business model to a circular one. Based on understanding of definitions of circular economy, it is necessary to provide a detailed note of processes in circular economy to conceptualize how stake holders can practice them in actual. This paper aims to identify and characterize the processes in circular economy and then conceptualize the anticipated impacts through using these processes in business models in different sectors in the economy.